PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT CIPTA SAMA ABADI KABUPATEN BOGOR - Branson Barus, Sony; Ratnawati, Whina (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of motivation on employee performance at PT Cipta Sama Abadi, Bogor Regency, to determine the influence of the work environment on employee performance at PT Cipta Sama Abadi, Bogor Regency, and to determine the simultaneous influence of motivation and work environment on employee performance at PT Cipta Sama. eternal Bogor district. The sampling technique used the Slovin formula method. The population in this study was 112 populations. The sample used was 88 respondents using questionnaire data collection techniques. The nature of the research used is quantitative. The data analysis methods used include validity testing, reliability testing, classical assumption testing, simple & multiple linear regression, correlation and determination coefficient testing, and hypothesis testing. Based on the research results, the influence of motivation has a significant effect on employee performance, which can be seen from the results of the count = 2.530, while table = 1.987 (icount > table) with a significance level of 0.000<0.050, the work environment has a significant effect on employee performance, which can be seen with the results of the icount = 4.742. table = 1.987 (tcount > table) with a significance level of 0.005 < 0.050. Motivation and the work environment have a significant effect on employee performance, which can be seen from the calculated f test results = 2.200 while f table = 3.10 (t count > t table) with a significance level of 0.007 < 0.050. The multiple regression equation is Y = 39.504 + 0.084X1 + 0.113X2+ e. The coefficient of determination test was 14.9% and the remaining 85.1% was influenced by other variables.